Application Of The Principles Of Carefulness And Accuracy For Notaries In Drafting Deeds (Study At The Notary Office Of Herny Wahdaniyah Wahab, S.H., M.Kn.) - Yudha Pradina, Sheilla (International Significance of Notary, 2024)
Abstract : A notary in his position as a public official who has the authority to make deeds, makes the deeds he makes have very perfect evidentiary power. In this case, all deeds made by a notary or before a notary must be carried out with the principles of prudence, thoroughness and responsibility, because notary is a position that is obtained from the trust given by the law and society. In this case, the formulation of the problem in this research is as follows (1) What is the form of the Principle of Prudence and Accuracy for Notaries in making Deeds (2) What are the Responsibilities of Notaries for deeds that have been made but there are errors or mistakes such as typos? and the identities of the parties are wrong. This research is included in empirical research using a qualitative research approach. In this research, there are the following conclusions. The forms of the principle of prudence and accuracy for notaries in making deeds are as follows: (1) The form of the principle of prudence that is applied and implemented is as follows: (1) verifying the facing data, ( 2) accommodate the wishes of the parties, (3) Review/double check the data and deeds made. The form of the prudential principle applied and implemented in this case is in accordance with the prudential principle in banking, namely the 4P formula: Personality, Purpose, Prospect, and Payment. The form of accuracy that can be carried out by a notary is to check/scrutinize the identity of the presenters, including signatures, photos, fingerprints, objects and deeds before/after being printed before/after being read in front of the presenter. (2) The responsibility of the Notary for deeds that have been made but contain errors or errors such as typos and incorrect identities of the parties is the Renvoi method. In this case, there is a form of civil liability that can be carried out by a notary if the error can cause losses. This is regulated in Article 1365 of the Civil Code.Keywords: Prudence, Accuracy, Responsibility